Peningkatan Kemampuan Mengenal Warna Melalui Metode Eksperimen Pada Anak KB Islamiyah Probolinggo - Wedya Puspita (Journal on Education, 2024)
Early childhood education is an important foundation in forming children's character and basic skills, including the ability to recognize colors. At KB Islamiyah Probolinggo, initial observations show that around 65% of children are not able to recognize colors well, indicating the need for more effective learning methods. This research aims to test the effectiveness of experimental methods in improving the ability to recognize colors in children at KB Islamiyah Probolinggo. This research uses a quasi-experimental design with a pre-test and post-test for two groups, namely the experimental group and the control group. The research sample consisted of 30 children who were divided randomly into two groups. The experimental group was given treatment with experimental learning methods for 8 weeks, while the control group continued to use conventional teaching methods. Data were collected through color recognition tests before and after intervention and analyzed using paired t tests and ANOVA. The results showed that the experimental group experienced a significant increase in color recognition ability compared to the control group. The average pre-test and post-test scores in the experimental group were 45 and 85 respectively, with an increase of 40%, while the control group increased from 47 to 60, an increase of 13%. The results of the t test and ANOVA showed significant differences between the two groups (t=8.25, p<0.01 for the experimental group and t=2.35, p<0.05 for the control group; F=10.47, p<0.01).